CARDIOVASCULAR EFFECTS OF AN ARGINASE II SELECTIVE INHIBITOR - Vladimir Yakushev; Mikhail Pokrovskii (Belgorod National Research University, 2016)
For the first time in vitro experiments there were studied the inhibitory activity and safety of potential molecules arginase II selective inhibitors from the group of norleucine derivatives. Also first the substance under the code ZB49-0010C from the group of norleucine derivatives showed the greatest selectivity and inhibitory activity against arginase II in experiments in vitro. However, this substance in vivo exerts dose-dependent hypotensive action and cardioprotective and endothelial protective effects on the L-NAME induced and homocysteine-induced endothelial dysfunction (ED), which are most pronounced at a dose of 10 mg/kg in intragastric administration. Endothelial protective effect consists of in preventing the increase of coefficient of endothelial dysfunction (CED) and the decrease in the concentration of stable metabolites of nitric oxide in the blood plasma. Cardioprotective effect consists of in preventing the increase of the level of left ventricular pressure during the test for adrenoreactivity and reducing of the cardiac reserve during the overload resistance test, and also in preventing the development of the left ventricular hypertrophy. As part of the study there was investigated the dose-dependent anti-ischemic effect of the arginase II selective inhibitor, substance ZB49-0010C on the chronic limb ischemia in rats, which most pronounced at a dose of 10 mg/kg and consists of in preventing the fall in microcirculatory level on the 29th day of the experiment in the ischemic limb and a protective effect based on the morphological examination of the muscle tissue.